Physical and oxidative stability of fish oil nanoemulsions produced by spontaneous emulsification: Effect of surfactant concentration and particle size. (November 2015) - Walker, Rebecca M.; Decker, Eric A.; McClements, David J.
Highlights: Fish oil nanoemulsions produced by low-energy method (spontaneous emulsification). Nanoemulsions were physically stable during storage at 37 °C for 14 days. Nanoemulsions produced by low- and high-energy methods had similar oxidative stability. Lipid oxidation was independent of initial particle size and surfactant level. Spontaneous emulsification may be useful for ω-3 fortification of clear foods. Abstract: Nanoemulsion-based delivery systems offer many potential benefits for incorporating omega-3 oils into foods and beverages. Nanoemulsions are gaining popularity because of their ease of preparation, small particle size, relatively high stability, and production of optically transparent emulsions. In this study, spontaneous emulsification, a low-energy method, was used to fabricate fish oil nanoemulsions. The influence of surfactant-to-oil-ratio on particle size and physical stability was evaluated. Optically transparent nanoemulsions were formed and maintained physical stability at 37 °C for 14 days. Furthermore, the effect of particle size and surfactant concentration on oxidative stability of these nanoemulsions was compared to emulsions produced by microfluidizer, a high-energy method. These nanoemulsions had similar oxidative stabilities at 55 °C for 14 days. These results demonstrate that spontaneous emulsification can produce fish oil nanoemulsions that are physically stable and oxidize at similar rates as traditionally prepared nanoemulsions, and therefore may be suitable for fortifying clear food systems.